2009
DOI: 10.1111/j.1365-3121.2009.00888.x
|View full text |Cite
|
Sign up to set email alerts
|

Intracontinental subduction: a possible mechanism for the Early Palaeozoic Orogen of SE China

Abstract: International audienceThe Early Palaeozoic Orogen of SE China consists of three litho-tectonic elements, from top to bottom: a sedimentary Upper Unit, a metamorphic Lower Unit and a gneissic basement. The boundaries between these units are flat lying, south directed, ductile decollements. The lower one is coeval with an amphibolite facies metamorphism (M1). The belt is reworked by migmatite-granite domes, high-temperature metamorphism (M2) and granitic plutons related to post-orogenic crustal melting. We date … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
201
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 337 publications
(205 citation statements)
references
References 39 publications
4
201
0
Order By: Relevance
“…Contemporaneous mantle-derived rocks have not been identified in these domains so far (e.g., Shu et al, 2008c;Wang et al, 2010). These observations, together with the Kwangsian thrust-dominated compressive setting of the eastern SCB (e.g., Charvet et al, 1996Charvet et al, , 2010Faure et al, 2009;Shu et al, 1991;1999), indicate an insignificant magma underplating into the crust. We propose that the generation of the granitic melts in the eastern SCB may have been controlled by crustal thickening under the condition of high heat production in the source.…”
Section: Partial Melting Of a Basement-dominant Component?mentioning
confidence: 90%
See 2 more Smart Citations
“…Contemporaneous mantle-derived rocks have not been identified in these domains so far (e.g., Shu et al, 2008c;Wang et al, 2010). These observations, together with the Kwangsian thrust-dominated compressive setting of the eastern SCB (e.g., Charvet et al, 1996Charvet et al, , 2010Faure et al, 2009;Shu et al, 1991;1999), indicate an insignificant magma underplating into the crust. We propose that the generation of the granitic melts in the eastern SCB may have been controlled by crustal thickening under the condition of high heat production in the source.…”
Section: Partial Melting Of a Basement-dominant Component?mentioning
confidence: 90%
“…However, Yu et al (2007) suggested that the Kwangsian orogenesis likely resulted from the amalgamation and collision of the Yangtze Block with northern Gondwanaland. Faure et al (2009) recently pointed out that the early Paleozoic Orogen of Southeast China is an intracontinental belt, in which decollements accommodated the northward subduction of the Cathaysia continent with no preceding oceanic subduction. Recent studies (e.g.…”
Section: Jiangshan-shaoxing Fault: a Reactivated Boundary During The mentioning
confidence: 99%
See 1 more Smart Citation
“…Controversies on the nature of both events for the SCB still exist, with the key disputing point on the subduction/collision scenario versus intracontinental regime (e.g., Charvet et al, 1999Charvet et al, , 2010Faure et al, 1996Faure et al, , 2009Guo et al, 1989;Holloway, 1982;Hsü et al, 1990;Li et al, 2011b;Liu and Xu, 1994;Ma et al, 2004;Shu et al, 2008aShu et al, , 2008bShu et al, , 2011Wang et al, 2005b;Y.J. Wang et al, 2007aY.J.…”
Section: Kwangsian and Indosinian Reworking Of The Eastern Scbmentioning
confidence: 99%
“…As for the nature of the orogeny, some researchers believed that the mountain-building event was the result of the finial closure of the Huanan/Paleotethys Ocean and subsequent collision of the Yangtze and Cathaysia Blocks (e.g., Guo et al, 1989;Hsü, 1994;Chen et al, 2006;Yan et al, 2006). However, the absence of the subduction-related rock associations (e.g., ophiolites, magmatic arc, subduction complexes and high-pressure metamorphic rocks) in the whole SCB convincingly precludes the existence of an ocean basin between the Yangtze and Cathaysia Blocks during early Paleozoic time, which led some researchers to propose an intracontinental orogenic event (e.g., Charvet et al, 1996Charvet et al, , 2010Faure et al, 2009;Li et al, 2010). More recently, on the basis of the fact that the 460-400 Ma event was mainly restricted to the Cathaysia Block, Zhao and Cawood (2012) further suggested that the early Paleozoic (460-430 Ma) orogeny in the Cathaysia Block was a continentcontinent collisional event.…”
Section: Geological Backgroundmentioning
confidence: 99%